EXTRACTION OF NIGELLA SATIVA SEEDS AT A PILOT SCALE AND THEIR EFFECTS ON THE FORMATION OF PSEUDOMONAS AERUGINOSA BIOFILMS - Didi, Amel; Didi, Mohamed Amine (Scientific Study & Research. Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2021)
The extraction of vegetable oils from aromatic and medicinal plants has been the subject of research in several recent studies. Because of their richness in secondary metabolisms which are part of the manufacture of drugs, food supplements and cosmetic products. We are interested in discontinuous solid-liquid extraction of seeds of Nigella sativa at a pilot scale. Biological and physicochemical analysis was carried out on the extracts of these seeds, in order to valuate them. The results have shown that the extracts of Nigella sativa seeds are very rich in fatty acids and polyphenols in addition to the presence of other nutrients such as vitamins, amino acids and free quinones which have shown potential in phytotherapy. The extracts of the plant prevents the formation of Pseudomonas Aeruginosa biofilms. This study has given very promising results with regard to the efficiency of the extracts on free radicals and bacterial strains.